1999
DOI: 10.1007/s002130050811
|View full text |Cite
|
Sign up to set email alerts
|

Oxytocin modulates psychotomimetic-induced deficits in sensorimotor gating

Abstract: Oxytocin plays an important role in the regulation of normal cognitive functions and behaviors, which are disturbed in schizophrenia. Several studies suggest that oxytocinergic function is abnormal in schizophrenia patients. Thus, oxytocin may be involved in the pathophysiology associated with this disorder. This study investigated the regulatory effects of oxytocin on deficits in prepulse inhibition (PPI) associated with schizophrenia. Prepulse inhibition (PPI) is an operational measure of sensorimotor gating… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

8
83
0
2

Year Published

2001
2001
2016
2016

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 111 publications
(93 citation statements)
references
References 36 publications
8
83
0
2
Order By: Relevance
“…Our results are consistent with a study in rats demonstrating PCPinduced disruptions of PPI can be ameliorated by pretreatment with Oxt. 27 They also found that Oxt pretreatment reduced the effects of Amp, but not Apo, on disrupted PPI. 27 The lack of genotypic effect observed following treatment with Amp or Apo suggests that the dopaminergic system, involved in the regulation of PPI, is less affected, if not normal, in OxtÀ/À mice.…”
Section: Discussionmentioning
confidence: 95%
See 2 more Smart Citations
“…Our results are consistent with a study in rats demonstrating PCPinduced disruptions of PPI can be ameliorated by pretreatment with Oxt. 27 They also found that Oxt pretreatment reduced the effects of Amp, but not Apo, on disrupted PPI. 27 The lack of genotypic effect observed following treatment with Amp or Apo suggests that the dopaminergic system, involved in the regulation of PPI, is less affected, if not normal, in OxtÀ/À mice.…”
Section: Discussionmentioning
confidence: 95%
“…Also in rats, pharma-cologically disrupted PPI can be restored with Oxt administration. 27 Consequently, it has been hypothesized that Oxt may act as an endogenous antipsychotic. 27,28 In 'normal' animals, PPI is disrupted by the administration of drugs such as apomorphine (Apo) that acts as an agonist at D1 and D2 family dopamine receptors and amphetamine (Amp) that releases and inhibits reuptake of dopamine, 29,30 as well as the noncompetitive N-methyl-D-aspartic acid (NMDA)/ glutamate receptor antagonist phencyclidine (PCP).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Whereas all antipsychotics tested can block amphetamine-induced disruption of PPI, only some drugs can block the PPI effects of non-competitive NMDA antagonists. These include several atypical antipsychotics (Bakshi and Geyer, 1995;Bakshi et al 1994;Swerdlow et al 1996), serotonin (Varty and Higgins 1995), alphaadrenergic antagonists (Bakshi and Geyer 1997), nitric oxide synthetase inhibitors , and some neuropeptides (Feifel and Reza 1999;Feifel et al 1999b). Thus, OLETF rats may have alterations in one or more of these systems making them less sensitive to the PPI disrupting effects of non-competitive NMDA antagonists.…”
Section: Discussionmentioning
confidence: 99%
“…Vasotocin and isotocin are the fish homologues of vasopressin and oxytocin, two nonapeptides closely associated with sociality in mammals (including affiliative and sexual behaviours [32]), plus social/ emotional processing, stress response modulation, learning and memory [33][34][35][36]. Oxytocin has antipsychotic properties [28,37,38] and has been shown to restore deficits in sensorimotor gating induced by MK-801 in rats [39]. The association between MK-801 exposure and isotocin/vasotocin may indicate an unexpected conservation with mammalian patterns in modulating aspects of glutamatergic signalling in fish, and may also reflect molecular stress and coping responses to cognitive disruption [33,34].…”
Section: Discussionmentioning
confidence: 99%